2010
DOI: 10.3109/08977194.2010.484424
|View full text |Cite
|
Sign up to set email alerts
|

Structural elements and allosteric mechanisms governing regulation and catalysis of CSK-family kinases and their inhibition of Src-family kinases

Abstract: C-terminal Src kinase (CSK) and CSK-homologous kinase (CHK) are endogenous inhibitors constraining the activity of the oncogenic Src-family kinases (SFKs) in cells. Both kinases suppress SFKs by selectively phosphorylating their consensus C-terminal regulatory tyrosine. In addition to phosphorylation, CHK can suppress SFKs by a unique non-catalytic inhibitory mechanism that involves tight binding of CHK to SFKs to form stable complexes. In this review, we discuss how allosteric regulators, phosphorylation, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 95 publications
1
32
0
Order By: Relevance
“…Tyr530 in c-Src and Tyr535 in c-Yes at the C-terminal region, however, are inhibitory in nature since their phosphorylation lead to a blockade of the corresponding SFK activity. Endogenous negative regulators of SFKs, namely C-terminal Src kinase (Csk) and Csk-homologous kinase (Chk), keep SFKs in an “off ” state in the absence of stimulation 48 and a conformational change as shown in Figure 2B would allow phosphorylation of the stimulatory tyrosine to activate SFKs. 33 It has been reported that the association of c-Src with the plasma membrane is relatively dynamic and is regulated by its intrinsic kinase activity and its SH2 domain 49 These observations thus indicate that SFKs are capable of interacting with a large number of partner proteins and substrates via their inherent SH domains, which pave the way for their ability to integrate and transmit diverse cellular signals.…”
Section: General Structure Of Sfks and A Comparison Between C-src Andmentioning
confidence: 99%
“…Tyr530 in c-Src and Tyr535 in c-Yes at the C-terminal region, however, are inhibitory in nature since their phosphorylation lead to a blockade of the corresponding SFK activity. Endogenous negative regulators of SFKs, namely C-terminal Src kinase (Csk) and Csk-homologous kinase (Chk), keep SFKs in an “off ” state in the absence of stimulation 48 and a conformational change as shown in Figure 2B would allow phosphorylation of the stimulatory tyrosine to activate SFKs. 33 It has been reported that the association of c-Src with the plasma membrane is relatively dynamic and is regulated by its intrinsic kinase activity and its SH2 domain 49 These observations thus indicate that SFKs are capable of interacting with a large number of partner proteins and substrates via their inherent SH domains, which pave the way for their ability to integrate and transmit diverse cellular signals.…”
Section: General Structure Of Sfks and A Comparison Between C-src Andmentioning
confidence: 99%
“…Further exploration of proximal regions via site-directed mutagenesis and alanine scanning studies has identified contacts that are deemed essential for kinase activation via the SH2 domain [21], [23]. As a modular enzyme, Csk's domain linkers also play key roles in domain packing and arrangement of the active kinase conformation [15]. A specific site in the SH2-kinase linker (residue 183), which packs against the small lobe of the kinase domain, is very sensitive to the size of its side chain (Phe in wild type Csk) and is essential for functional flexibility and Csk activation via the SH2 domain [24].…”
Section: Resultsmentioning
confidence: 99%
“…Stabilizing effects are seen in other regions that correspond to distal motifs and are part of the catalytic machinery. Such long-range coupled effects underlie the intrinsic cross-domain communications that are integral to Csk's function as a multidomain enzyme [15]. Notably, the conserved Arg313 of the catalytic loop ( i −1 to the catalytic base) is overall more stable in the variant trajectories than in the wild type.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations